Dietary Supplementation of ε-Polylysine Beneficially Affects Ileal Microbiota Structure and Function in Ningxiang Pigs - Zhang, Xuelei; Hou, Zhenping; Xu, Baoyang; Xie, Chunlin; Wang, Zhichang; Yu, Xia; Wu, Duanqin; Yan, Xianghua; Dai, Qiuzhong (Frontiers in Microbiology, 2020)
Intestinal microbiota plays an important role in the health of animals. However, little is known about the gut microbiota in Ningxiang pigs. Thus, we investigated how dietary supplementation with different ε-polylysine concentrations (0, 20, 40, 80, and 160 ppm) affected the ileal microbiota in Ningxiang pigs using a replicated 5 × 5 Latin square method. Each experimental period included 10 days for diet adaptation, three days for feces collection and two days for digesta collection. The ileal contents were collected and used for sequencing of the V3–V4 hypervariable region of the 16S rRNA gene. The results revealed that ε-polylysine significantly decreased the digestibility of crude protein and crude fiber, as well as the utilization of metabolizable energy (P < 0.05). The relative abundances of 19 bacterial genera significantly increased, while those of 26 genera significantly decreased (P < 0.05). In addition, ε-polylysine increased the abundance of some bacteria (e.g., Faecalibacterium, Bifidobacterium, and lactic acid bacteria) and inhibited some other bacteria (e.g., Micrococcaceae, Acinetobacter, Anaerococcus, Peptoniphilus, Dehalobacterium, Finegoldia, Treponema, and Brevundimonas). Furthermore, based on the 16S rRNA gene data and data from the precalculated GreenGenes database, bacterial communities in the ileal contents exhibited enhanced functional maturation, including changes in the metabolism of carbohydrates, amino acids (e.g., alanine, lysine, tryptophan, cysteine, and methionine), cofactors, and vitamins (e.g., biotin, thiamine, and folate), as well as in the activity of the insulin signaling pathway. This study suggests that ε-polylysine may influence the utilization of feed nutrients by Ningxiang pigs, including proteins, lipids, metabolizable energy, and fiber, by regulating the gut microbiota.